Thermal bonding of microfluidic devices : factors that affect interfacial strength of similar and dissimilar cyclic olefin copolymers - Roy, Sunanda (2013)
Thermal bonding of the same polymer is an important method for obtaining good thermal sealing between two polymeric substrates in microfluidic devices. It is worthwhile to use different grades of the same polymer which have different glass transition temperatures (Tg) because no change in microchannel profile and dimensions would occur in the higher Tg substrate during thermal bonding. However, apart from using different grades of a polymer with different Tg, there is no fundamental basis for the selection of suitable substrate pairs. Thus an in-depth study of the thermal bond strength of different grades of TOPAS cyclic olefin copolymer (COC) was conducted. The strength development and chain inter-diffusion across the bonded interface between different TOPAS grades was studied, and the influence of molecular weight (Mw) and bonding temperature was considered. Bonding in both symmetric (between two substrates of the same COC grade) and non-symmetric interfaces (between two substrates of different COC grades) was compared. Bonding was conducted at both below and above the Tg. The thermal bond strengths were assessed from lap shear specimens prepared using a range of bonding temperature, time and pressure. Thermal bonding between 5013 and 6015 polymer substrates at 125 °C for 6 min time under 2 MPa pressure was found to be the most favorable conditions at which no deformation in the geometry of the COC microchannel has been observed. The failure surfaces of the specimens were characterized by scanning electron microscopy (SEM). Through the above, a basis for selecting different grades of TOPAS to obtain thermally bonded COC microfluidic devices with high strength was developed. The principles established are believed to be applicable to other polymeric microfluidic chips.